2011
DOI: 10.1016/j.jep.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of extract and fractions from the leaves of Byrsonima intermedia A. Juss. in rats

Abstract: BiAE and the individual EtOAc and aqueous fractions of Byrsonima intermedia exhibited chronic and acute anti-inflammatory efficacy in rats, which supports previous claims of its use in traditional medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…Moreira et al . () reported that the aqueous extract of B. intermedia leaves exhibited potent anti‐inflammatory activity in animal models by reducing carrageenan‐induced paw edema and granuloma formation in a chronic inflammation model; this activity was attributed to the presence of catechin and flavonoids. Saldanha et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreira et al . () reported that the aqueous extract of B. intermedia leaves exhibited potent anti‐inflammatory activity in animal models by reducing carrageenan‐induced paw edema and granuloma formation in a chronic inflammation model; this activity was attributed to the presence of catechin and flavonoids. Saldanha et al .…”
Section: Resultsmentioning
confidence: 99%
“…Studies of the genus Byrsonima focus mainly on antimicrobial activity against a range of bacteria, enterobacteria, mycobacteria, protozoa and fungi related to gastrointestinal and skin diseases (Guilhon-Simplicio and Pereira, 2011). In last few years, some studies on other biological properties have been reported in different species and parts of plants, such as antioxidant activity (Gordon et al, 2011;Mariutti et al, 2014;Vargas et al, 2016), central nervous system depressant activity (Herrera-Ruiz et al, 2011), anti-diabetes activity (Perez-Gutierrez et al, 2010, Pérez-Gutierrez andRamirez, 2016), and anti-inflammatory activity (Maldini et al, 2009;Moreira et al, 2011;Saldanha et al, 2016a;Saldanha et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical and pharmacological data obtained more recently from the Byrsonima genus can justify its use in folk medicine. Anti-inflammatory [6], gastroprotective, antidiarrheal, antimicrobial [7], and antitubercular activities [8], for instance, have been reported. Phytochemical analyses of the genus showed basically phenolic compounds such as quercetin derivatives and proanthocyanidins [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The cotton pellet-induced granuloma tissue formation animal model was established as previously described (8), but with minor modifications. Briefly, rats were anesthetized with 350 mg/kg chloral hydrate and two sterilized cotton pellets, that weighed 20 mg each, were implanted subcutaneously on each side of the nape through a small ventral incision in the nape of the rats.…”
Section: Methodsmentioning
confidence: 99%